2010
DOI: 10.1001/archinternmed.2010.345
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Follow-up Visit and 30-Day Emergency Department Visit and Readmission in Patients Hospitalized for Chronic Obstructive Pulmonary Disease

Abstract: Background Readmissions in patients with chronic obstructive pulmonary disease (COPD) are common and costly. We examined the effect of early follow-up visit with patient’s primary care physician (PCP) or pulmonologist following acute hospitalization on the 30-day risk of an emergency department (ER) visit and readmission. Methods We conducted a retrospective cohort study of fee-for-service Medicare beneficiaries with an identifiable PCP who were hospitalized for COPD between 1996 and 2006. Three or more visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
188
2
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(199 citation statements)
references
References 31 publications
7
188
2
2
Order By: Relevance
“…The effect of early visit on readmission and mortality, although more pronounced in the first week (days [8][9][10][11][12][13][14][15], persisted during the entire follow-up period. Table 4 displays the results of prespecified subgroup analyses.…”
Section: Propensity-score-matched Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of early visit on readmission and mortality, although more pronounced in the first week (days [8][9][10][11][12][13][14][15], persisted during the entire follow-up period. Table 4 displays the results of prespecified subgroup analyses.…”
Section: Propensity-score-matched Cohortmentioning
confidence: 99%
“…Although this policy is set, the relationship between early clinician followup and reduced readmission rates is inconsistent across medical conditions. (10)(11)(12)(13) No data on this association exist in patients with cirrhosis.…”
mentioning
confidence: 99%
“…10,11 COPD, for instance, is the third leading cause of 30-day hospital readmissions. 12 Clinical practice guidelines for both asthma and COPD recommend that clinicians assess and teach respiratory inhaler technique at all points of care, including during hospitalizations. 13,14 However, studies that we and others have conducted have found that the vast majority of patients hospitalized with asthma or COPD misuse their inhalers.…”
Section: Introductionmentioning
confidence: 99%
“…Step 2: Follow-up Appointment With PCP or Most Appropriate Continuity Provider Early follow-up with an appropriate outpatient provider has been associated with reduced hospital readmissions for patients with congestive heart failure, chronic obstructive pulmonary disease, and psychiatric illnesses, [26][27][28][29] but this finding has not been consistent across all patient populations. 5,30 It is not well understood if the follow-up appointment needs to be within a specific time frame, especially if the patient is already being "touched" once by the system through the posthospitalization call.…”
Section: After Hospital Dischargementioning
confidence: 99%